2020
DOI: 10.20473/ijosh.v9i3.2020.349-359
|View full text |Cite
|
Sign up to set email alerts
|

The Factors of Needlestick Injury on Healthcare Workers at the Hospital of Bojonegoro

Abstract: Introduction: Needlestick injury is the most frequent accidents encountered by healthcare workers in the hospital. Needlestick injury can expose healthcare workers to the risk of communicable diseases infection. This study was conducted in one of the hospitals in Bojonegoro. Healthcare workers in the inpatient installation and laboratory room have a potential for needlestick injury since they often use needles in their work activities. The aim of this study was to analyze the needlestick injury-related factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
1
0
2
Order By: Relevance
“…The data on occupational accidents in Indonesia, especially in the healthcare sector, has not been well reported. A previous study in Bojonegoro regional public hospital showed that the incidence of needlestick injuries among nurses in one year reached 29 times (Fitria et al, 2020). Although data related to the hazards due to occupational accidents in Indonesia have consent that respondents should complete for their voluntary participation.…”
Section: Methodsmentioning
confidence: 99%
“…The data on occupational accidents in Indonesia, especially in the healthcare sector, has not been well reported. A previous study in Bojonegoro regional public hospital showed that the incidence of needlestick injuries among nurses in one year reached 29 times (Fitria et al, 2020). Although data related to the hazards due to occupational accidents in Indonesia have consent that respondents should complete for their voluntary participation.…”
Section: Methodsmentioning
confidence: 99%
“…Organization bahwa cedera jarum suntik dapat menyebabkan lebih banyak risiko Hepatitis tipe B, Hepatitis tipe C, dan infeksi HIV (6).…”
Section: Hal Ini Sejalan Dengan Pernyataan World Health Organization ...unclassified
“…Faktor penting lain yang berhubungan dengan terjadinya needle stick injury adalah kesadaran tenaga Kesehatan. Pada penelitian lain yaitu di ketahui bahwa kejadian needle stick injury disebabkan oleh faktor tingkat Pendidikan (p= 0.024) dan unsafe action (p= 0.002) dari tenaga Kesehatan (6).…”
Section: Hal Ini Sejalan Dengan Pernyataan World Health Organization ...unclassified